Media and technology in education: A constructivist view - Fosnot, Catherine Twomey (Educational Technology Research and Development, 1984)
This paper is a version of the seventh ECTJ/ERIC-IR Young Scholar Paper, an annual award initiated to stimulate writing by young professionals in the field of instructional technology. Preparation of the paper was supported by the ERIC Clearinghouse on Information Resources at Syracuse, NY. - Ed. © 1984 Association for Educational Communications and Technology.
Keywords: dept.edu